AIKII: An AI‐Enhanced Knowledge Interactive Interface for Knowledge Representation in Educational Games - Liu, Dake; Zhao, Huiwen; Tang, Wen; Yang, Wenwen (Computer animation and virtual worlds, 2025)
ABSTRACT The use of generative AI to create responsive and adaptive game content has attracted considerable interest within the educational game design community, highlighting its potential as a tool for enhancing players' understanding of in‐game knowledge. However, designing effective player‐AI interaction to support knowledge representation remains unexplored. This paper presents AIKII, an AI‐enhanced Knowledge Interaction Interface designed to facilitate knowledge representation in educational games. AIKII employs various interaction channels to represent in‐game knowledge and support player engagement. To investigate its effectiveness and user learning experience, we implemented AIKII into The Journey of Poetry, an educational game centered on learning Chinese poetry, and conducted interviews with university students. The results demonstrated that our method fosters contextual and reflective connections between players and in‐game knowledge, enhancing player autonomy and immersion.